PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KABUPATEN MAMASA - Indra Wilyanti; Aco Dahrul Saharuddin; Sri Yuyun (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2021)
The purpose of this study was to determine the effect of leadership style on employee performance at the Mamasa Regency DPRD secretariat office and employee performance at the Mamasa Regency DPRD secretariat office. The type of research that the author uses in this research is empirical research. which departs from empirical data that ends with the discovery. Empirical research is intended as an effort to approach the problem under study with a legal nature that is in accordance with the reality faced in society. The results of the study indicate that the workplace, compensation, and leadership attitudes are factors that together have a significant effect on the work motivation of the Mamasa Regency DPRD Secretariat employees and provide an indication that the most dominant work motivation affecting the Mamasa Regency DPRD Secretariat employees is the workplace factor.